Study on production and utilization of minor millets in Madhya Pradesh - DEVI, ASHA; P, ANBUKKANI; SINGH, ALKA; MALHOTRA, S K; JHA, GIRISH K; PANGHAL, PRADEEP (The Indian Journal of Agricultural Sciences, 2024)
Neglected and underutilized species (NUS) worldwide are gaining attention as they are suited to sustainable food systems offering food and nutritional security to people in marginal regions. Minor millets are one such group of crop species that can be utilized to supplement the cereal-centric diet. But they are largely neglected in terms of research and development, policy support, and consumer demand. Present study was carried out during 2020 in selected districts of Madhya Pradesh to explore the production, consumption and utilization of minor millets and to identify the problem faced by the farmers at the field level. Farmers grow local varieties of millets with poor management under rainfed conditions. The price received by the farmers vary widely, although it is economically viable. Most sample farmers were unaware of the possibility of processing the grain into various products that suit consumer demand and fetch better prices. They perceive the unavailability of high-yielding variety as the major production constraint. The revival of millets requires a multidimensional approach involving government support, research and development, awareness campaigns, and consumer demand.